Collaboration between Teachers and Islamic Religious Leaders in Improving Al-Qur'an Literacy: Kolaborasi Guru dan Rohani Islam dalam Penguatan Literasi Al-Qur’an - Nisak, Siti Latifatun; Nugroho, Puspo (Halaqa: Islamic Education Journal, 2025)
This study aims to examine the implementation of strengthening Al-Qur'an literacy through a program designed by Islamic Religious Education teachers in collaboration with the school's Rohis organization. The study focuses on two main activities: the literacy or tadarus Al-Qur'an program held for 15 minutes before lessons begin, and the BTA (Baca Tulis Al-Qur'an) program intended for students who still experience difficulties in reading the Al-Qur'an. Using a qualitative method with data collected through observation, interviews, and documentation, the findings show that students demonstrate high enthusiasm in participating in the program, although challenges remain in maintaining discipline and activity consistency. Through motivation, guidance, and strong collaboration between teachers and Rohis members, the Al-Qur'an literacy strengthening program can be implemented effectively and sustainably. This study is expected to contribute to efforts in maintaining and improving Al-Qur'an literacy programs in schools.